Routledge handbook of migration and development - Bastia, Tanja; Skeldon, Ronald (Routledge international handbooks, 2020)
Part 1. Conceptual perspectives and approaches -- Part 2. Economic and social dimensions: Poverty and inequalities -- Part 3. Families and social policy -- Part 4. Policies, rights and interventions -- Part 5. Key challenges for migration and development -- Part 6. Migration corridors: Large and small -- Part 7. Translating migration and development -- In lieu of a conclusion: Tracing the way forward in migration and development.